Praise And Complaint Toward Hotel Staff: A Corpus-Based Analysis Of English-Language Reviews Of Indonesian Hotels On Booking.Com - Ahmad Zaidi; Anandya Asprillia (Journal of Language and Applied Linguistics, 2026)
This study addresses the challenge of systematically processing the vast volume of qualitative online reviews, which significantly influence hotel reputations but are prone to researcher bias when analysed manually. The primary goal is to uncover the linguistic patterns of appraisal that shape international guest satisfaction within the Indonesian hospitality context, focusing on how guests evaluate both physical facilities and service performance. The research utilised a corpus-based approach, analysing a dataset of English-language reviews scraped from Booking.com. These data were processed using AntConc software, applying the Appraisal Framework—specifically the dimensions of Attitude, Graduation, and Engagement—to categorise and quantify evaluative tokens. Collocation analysis was further employed to identify the recurring themes and targets of both praise and complaints. The results demonstrate that guest satisfaction is primarily driven by Appreciation of the physical surroundings and Judgement of staff performance. Within the Appreciation dimension, "Overall Impression" and "Comfort" are the leading evaluative targets. In the Judgement dimension, guests are over eleven times more likely to praise staff for Courtesy, such as being "friendly" and "helpful," than for technical Professionalism. Furthermore, the analysis of Graduation reveals a heavy reliance on Force: Intensification to signal maximal commitment to praise. Regarding Engagement, guests frequently use Countering resources (e.g., "but") to present "balanced" reviews that build solidarity with potential readers. The study concludes that while Indonesian hotels excel in interpersonal warmth and emotional labour, managers must prioritise improving operational efficiency and technical professionalism to match global standards. These findings provide a systematic framework for understanding how service quality and physical amenities shape digital reputations in the competitive tourism industry.